Is It Really Another Foreign Body? - Li Yun, Lim; Shamina Sara, Moses (Malaysian Paediatrics Association, 2022)
A 4-year-old boy was referred to our ENT clinic for foreign body (white bead) in the right ear. The white bead was removed successfully without much struggle from the boy. However, the repeated otoscope was done and the findings was seen in Figure 1. Further history taking, the boy did not have any frequent ear infections or problems. His pure tone audiometry showed normal hearing bilaterally.